The seismicity of the Carpathians in 2022 - Verbytskyi, S.T.; Pronyshyn, R.S.; Prokopyshyn, V.I.; Stetskiv, A.T.; Nischimenko, I.M.; Keleman, I.M.; Gerasymenyuk, G.A. (Geofizicheskiy Zhurnal, 2024)
According to the results of observations at the seismic stations of the Carpathian region of Ukraine in 2022, the main parameters of 50 earthquakes in the range of energy classes KR=5.7÷13.7 were obtained. The parameters of seismometric equipment at active seismic stations are given. A catalog of earthquakes, their distribution by regions and energy classes, a map of epicenters, graphs of seismic energy release, and the number of earthquakes in the region by month are presented. A brief description of the seismicity of certain seismically active areas of the Carpathian region is given. The total energy allocated to the region was ΣЕ=5.06·1013 J, which is higher than last year’s level of ΣЕ=3.13·1012 J. This year, increased seismic activity was observed in the Vrancea Mountains, where 20 earthquakes of energy class KR=9.1÷13.7 were recorded. Their total seismic energy was ΣE=5.06·1013J. The foci of the Vrancea earthquakes are concentrated at a depth of h=80÷152 km (18 events) and h=20 km (2 events). 10 earthquakes with energy class KR=5.8÷8.0 were registered in Transcarpathia. Their total seismic energy was ΣE=2.78·108 J. The strongest was recorded on March 28 with KR=8.0 at 05h01m at a depth of h=2.4 km. For the past seven years, Transcarpathia has been practically in a seismic lull. On the territory of Bukovyna this year, there is also a decrease in seismic activity compared to 2021. A total of 9 earthquakes with energy class KR=6.9÷8.4 and total seismic energy ΣЕ=8.41·108 J were registered here. The foci of earthquakes are in the earth’s crust at a depth of h=1.8÷15 km. In seismically active areas such as the Southern Carpathians, Transylvania, and Bacau, only one earthquake was recorded in 2022, while no event was recorded in the Kryšana and Banat regions. The regional Carpathian hodograph was used to determine the main parameters of earthquakes in Transcarpathia, and the Jeffreys-Bullen hodograph was used for earthquakes in the Vrancea zone and six other regions.